2021
DOI: 10.1029/2020sw002670
|View full text |Cite
|
Sign up to set email alerts
|

A Summary of National Oceanic and Atmospheric Administration Space Weather Prediction Center Proton Event Forecast Performance and Skill

Abstract: The ≥ 10 MeV proton Warnings have a Probability of Detection of 91% and a False Alarm Ratio 24% with a median lead time of 88 minutes.• The ≥ 100 MeV proton Warnings have a Probability of Detection of 53% and a False Alarm Ratio 38% with a median lead time of 10 minutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 42 publications
(67 reference statements)
0
46
0
Order By: Relevance
“…Regarding SEP predictions, SEPMOD requires the existence of a shock-observer magnetic field connection and the predicted SEP properties depend on the shock parameters at the connection point. Here we consider the three main areas that were identified by Bain et al (2021) to be of high importance (see also the Introduction), i.e. SEP onset time, event duration, and peak fluxes.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding SEP predictions, SEPMOD requires the existence of a shock-observer magnetic field connection and the predicted SEP properties depend on the shock parameters at the connection point. Here we consider the three main areas that were identified by Bain et al (2021) to be of high importance (see also the Introduction), i.e. SEP onset time, event duration, and peak fluxes.…”
Section: Discussionmentioning
confidence: 99%
“…The probabilities for the days when the reports were not issued were obtained by interpolation from the neighboring days. An extensive study of the SWPC NOAA SPE probabilities was recently performed by Bain et al (2021); we direct the readers to this study for more details about the operational forecasts.…”
Section: Daily Swpc Noaa Proton Event Probabilitiesmentioning
confidence: 99%
“…The current operational daily forecasting of > 10 MeV > 10 pfu SPEs relies on a statistics-based approach, plus a human forecaster to correct the predictions (Balch 1999(Balch , 2008Bain et al 2021). This approach has been validated over several solar cycles.…”
Section: Introductionmentioning
confidence: 99%
“…International efforts (see e.g., the SEP Validation Team: https://ccmc.gsfc.nasa.gov/assessment/topics/helio-sep.php) are underway to assess the current status of SEP forecasting and to establish community-wide metrics. Recently, Bain et al (2021) assessed the performance of the National Oceanic and Atmospheric Administration's Space Weather Prediction Center (NOAA/SWPC) proton event forecasts, finding for ≥10 MeV (≥100 MeV) proton warnings a probability of detection of 91% (53%) and a false alarm ratio of 24% (38%), with a median lead time of 88 min (10 min). The authors suggested that these results may serve as a benchmark for SEP models that can operate in a nowcast setting, and noted that a particular challenge is to accurately predict the onset, peak, and end times and fluxes of SEP events in different energy ranges.…”
Section: Introductionmentioning
confidence: 99%